2010
DOI: 10.1111/j.1439-0426.2010.01400.x
|View full text |Cite
|
Sign up to set email alerts
|

Mouth development in the Senegal bichirPolypterus senegalusdoes not involve the oropharyngeal membrane: possible implications for the ecto-endoderm boundary and tooth initiation

Abstract: Summary Polypterid fishes are considered the basal‐most group of extant actinopterygians and thus may serve as a direct link to understand the evolution of the first bony fishes. Embryonic and larval specimens, however, are extremely scarce, making it difficult to study their developmental patterns and processes. During the past few years we collected many embryos and larvae of the Senegal bichir Polypterus senegalus and in this paper we describe some novel observations concerning the supposed ecto‐endoderm bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Kerr (), Bartsch et al (), Diedhiou and Bartsch (), and Kralovic et al () previously staged the development of P. senegalus . Kerr () and Diedhiou and Bartsch () staged mainly before yolk exhaustion.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Kerr (), Bartsch et al (), Diedhiou and Bartsch (), and Kralovic et al () previously staged the development of P. senegalus . Kerr () and Diedhiou and Bartsch () staged mainly before yolk exhaustion.…”
Section: Methodsmentioning
confidence: 99%
“…The present study contributes to our understanding of the morphology of the opercular muscles in the extinct primitive actinopterygians. Kerr (1907), Bartsch et al (1997), Diedhiou and Bartsch (2009), and Kralovic et al (2010) previously staged the development of P. senegalus. Kerr (1907) and Diedhiou and Bartsch (2009) staged mainly before yolk exhaustion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the rupture of the buccopharyngeal membrane initiates secondary mouth development (Soukup et al, ). In some anamniotes, the stomodeum has been implicated in tooth induction (bichir, Kralovic et al, ; salamanders, Lumsden, ; caecilians, Wake, ).…”
Section: Discussionmentioning
confidence: 99%
“…An extant group of actinopterygians are the polypteriformes (polypterus or bichirs), and are considered by many to be the definitive representative of a actinopterygian “bauplan” (Bartsch, Gemballa, & Piotrowski, ; Kralovic, Horáček, & Cerny, ). Polypteriformes are bimodal respirators, using internal gills in water and paired dorsal spiracles to inhale air from the water surface (J.…”
Section: Evolution Of Jaws In Osteichthyesmentioning
confidence: 99%